Pleiotrophin Exerts Its Migration and Invasion Effect through the Neuropilin-1 Pathway - Rania Elahouel; Charly Blanc; Gilles Carpentier; Sophie Frechault; Ilaria Cascone; Damien Destouches; Jean Delbé; José Courty; Yamina Hamma-Kourbali (Neoplasia: An International Journal for Oncology Research, 2015)
Pleiotrophin (PTN) is a pleiotropic growth factor that exhibits angiogenic properties and is involved in tumor growth and metastasis. Although it has been shown that PTN is expressed in tumor cells, few studies have investigated its receptors and their involvement in cell migration and invasion. Neuropilin-1 (NRP-1) is a receptor for multiple growth factors that mediates cell motility and plays an important role in angiogenesis and tumor progression. Here we provide evidence for the first time that NRP-1 is crucial for biological activities of PTN. We found that PTN interacted directly with NRP-1 through its thrombospondin type-I repeat domains. Importantly, binding of PTN to NRP-1 stimulated the internalization and recycling of NRP-1 at the cell surface. Invalidation of NRP-1 by RNA interference in human carcinoma cells inhibited PTN-induced intracellular signaling of the serine-threonine kinase, mitogen-activated protein MAP kinase, and focal adhesion kinase pathways. Accordingly, NRP-1 silencing or blocking by antibody inhibited PTN-induced human umbilical vein endothelial cell migration and tumor cell invasion. These results suggest that NRP-1/PTN interaction provides a novel mechanism for controlling the response of endothelial and tumoral cells to PTN and may explain, at least in part, how PTN contributes to tumor angiogenesis and cancer progression.